PRESCRIPTION AND ADEQUACY OF HEMODIALYSIS - Widiana, I Gde Raka (Medicina; Vol 44 No 1 (2013): Januari 2013)
Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 Physiologically, uremic syndrome is a pollutional phenomenone of body fluid caused by uremic substance retention due to failing kidney. Hemodialysis (HD) is a substitution therapy to replace native kidney to filter out the toxic substances. The clearance capacity can be measured using urea kinetic modeling, where urea is used as a marker. Prescription of HD will produced prescribed KT/V, namely the amount of HD doses given. On the other hand delivered KT/V is real clearance effect occurred in the body. Each component of dialysis machine can be adjusted to produce adequate delivered KT/V. This KT/V has also to be adjusted with weekly frequency of HD and residual function of the native kidney. Value of KT/V in each HD session according the consensus has to be attained in order the patient live a better life longer /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: hemodialysis - urea kinetic modeling - KT/V – hemodialysis adequacy